The accuracy of laser fluorescence (DIAGNOdent) in assessing caries lesion activity on root surfaces, around crown margins, and in furcations in older adults - Chelsea Mitchell; Hiba Zaku; Peter Milgrom; Lloyd Mancl; David B. Prince (Nature Publishing Group, 2021)
Abstract The authors conducted a case series to assess accuracy of DIAGNOdent (DD) in assessment of activity of dental caries lesions in root surfaces and in furcations and at crown margins. The study was a prospective, single center case series. The patients were 123 adults (age ≥ 55 years). To be included, a patient needed to have at least one active root caries lesion. The study was conducted at the Roseman College of Dental Medicine in South Jordan, Utah, USA and at area nursing homes. Lesions were rinsed and dried with air, and DD readings were obtained. Lesions were then isolated and 38% silver diamine fluoride was applied repeatedly for two minutes with a microbrush. DD readings and treatments were repeated every six months. Mean DD values were significantly different between active (unarrested) and inactive (arrested) caries for all comparisons, p-value < 0.0001. The optimal cut-off values for DD were between 20 and 35 except optimal cut-offs were higher for furcation and crown margin surfaces, particularly in the posterior (optimal cut-offs 40-45). This study demonstrates DD is a potentially valuable tool for assessing lesion activity in root surfaces, at restoration margins, and in furcations.